Improved working memory performance following administration of a single dose of American ginseng (Panax quinquefolius L.) to healthy middle‐age adults. (March 2015) - Ossoukhova, Anastasia; Owen, Lauren; Savage, Karen; Meyer, Marjolaine; Ibarra, Alvin; Roller, Marc; Pipingas, Andrew; Wesnes, Keith; Scholey, Andrew
<x xml:space="preserve">Abstract</x> Objective A ginsenoside‐rich extract of American ginseng (Panax quinquefolius L.), CereboostTM, was previously shown to improve working memory and mood in healthy young individuals. The present study represented a partial replication investigating whether these effects extended to healthy middle‐aged individuals. Methods Fifty‐two healthy volunteers (40–60 years old, mean age 51.63) received 200 mg of P. quinquefolius or a matching placebo according to a double‐blind, placebo‐controlled, balanced, crossover design. The Cognitive Drug Research battery and the Computerised Mental Performance Assessment System were used to evaluate cognitive performance at baseline then 1, 3 and 6 h following treatment. Blood glucose and mood were co‐monitored. Results Compared with placebo, P. quinquefolius improved cognitive performance on 'Working Memory' factor at 3 h. Similar effects were observed in one of the two tasks making up this factor, spatial working memory. There were no significant effects on mood or blood glucose levels. Conclusions These data confirm that P. quinquefolius can acutely benefit working memory and extend the age range of this effect to middle‐aged individuals. These changes are unlikely to be underpinned by modulation of blood glucose in this population. Copyright © 2015 John Wiley & Sons, Ltd.